Anxiety Level Among Teacher Education Students - Ma. Erenita V. Bahian (Health Notions, 2018)
The present study investigated the level of anxiety among freshmen non-mathematics teacher education students. Using the statistics, it is geared to determine associations if any between their level of anxiety and demographic profiles. The researcher utilized quantitative descriptive-survey design to 170 respondents who were purposively chosen using pre-selection criteria. A 10-item Likert scale researcher-developed questionnaire, which underwent reliability test, was used to satisfy the intention. Data analyses were carried out statistically using Statistical Package for Social Sciences version 23.0. Results showed most of the respondents were females, aging from 15-19 years old. The findings revealed that respondents agree that they sometimes feel anxious in classroom mathematics class, and fear is felt during examination and board-related activities. There was association between respondent’s age and gender to the level of anxiety in learning the course to non-mathematics major students. Furthermore, the result divulged that older students often experienced higher level of anxiety than younger age, while female are more enxious than men during mathematics classes. The study recommends to utilize its findings to determine etiology of anxiety and its corresponding intervention in the limelight of instruction. Keywords: Anxiety, Anxiety level, Teacher education, Education, Education students